Computed Tomography Findings in Patients with Seizure Disorder - Acharya, Sumnima; Tiwari, Awadesh; Shrestha, Amit; Sharma, Rupesh; Shakya, Raju (Journal of Lumbini Medical College, 2017)
Introduction: Seizure occurs in up to 10% of the population, whereas epilepsy is a chronic disease characterized by recurrent seizures that may affect up to 2% of the population. Modern neuroimaging is useful in diagnosis of abnormalities  underlying  the  epilepsies,  but  the  information  provided  by  imaging  techniques  can  also  contribute to proper classification of certain epileptic disorders and can delineate the genetics of some underlying syndromes. Neuroimaging is even more important for those patients who have medically intractable seizures. This study was carried out to establish different etiologies of seizures, to correlate the clinical data and radiological findings in cases of seizure, and to identify the common etiologies in different types of seizures.Methods: This was a retrospective hospital-based study conducted in the Department of Radio diagnosis of Lumbini Medical College Teaching Hospital. Records of patients of past two years, admitted in any department of the hospital with history of seizure disorder and underwent a Computed Tomography (CT) of brain were included. The CT patterns were assessed and the data were tabulated and statistically analyzed.Results: There were a total of 480 cases out of which 263 (55%) were male and 217 (45%) were female with M:F ratio of 1.2:1. Generalized seizure was more frequent than partial seizure in  both  gender.  In  274  cases  of  generalized  seizures,  CT  scan  findings  were  abnormal  in  151  cases  and  normal finding  observed  in  123  cases.  In  206  cases  of  partial  seizures,  125  cases  were  abnormal  and  81  having  normal CT  scan  findings. Age  wise  distribution  showed  highest  number  (n=218)  of  cases  in  young  group  (60 yr). The most common cause of seizure was calcified granuloma (n=79, 16.5%) followed by neurocysticercosis (NCC, n=64, 13%). Diffuse cerebral edema, sub-arachnoid hemorrhage, and hydrocephalus was seen only in lower age group particularly among 1-20 years. Infarct and diffuse cortical atrophy were most common cause of seizure in older age group. NCC and tuberculoma are the most common cause of partial seizure whereas cerebral infarcts, hemorrhage, malignancy, diffuse cortical atrophy are the most common cause of complex seizure. Few rare diseases like Fahr disease and tuberous sclerosis were also found in CT scan of seizure patients. Conclusion: NCC and tuberculoma are the most common cause of partial seizure whereas cerebral infarcts, hemorrhage, malignancy, and diffuse cortical atrophy are the most common cause of complex seizure. CT scan plays an important role as a preliminary tool in radiological assessment of patients presenting with seizures.DOI: https://doi.org/10.22502/jlmc.v4i1.86J. Lumbini. Med. Coll. Vol 4, No 1, Jan-June 2016, page: 7-10